PERANCANGAN SISTEM INFORMASI LAPORAN KEUANGAN UMKM FOODY BESTIE BERBASIS WEB - Gelam Alfarisi (2022)
Technology has an important role and has an impact on human activities and lives, not only individuals, but small businesses also feel the development of technology. With technology, it can provide effectiveness in the business processes of a small business to improve the quality of its services in order to compete with its competitors. However, Foody Bestie still haven't utilized technology to its full potential. Foody Bestie still uses a manual system, so that the financial reports provided to the owner take a long time. In addition, data duplication and data corruption can occur. Based on this, the authors built a web-based Foody Bestie system to assist Foody Bestie in improving financial reports. The method used in system design is the waterfall method and PIECES as a system analysis method. The language used to build the system is PHP and the database used is MySQL. With the construction of this web, Egg Roll Bestie has been able to record financial reports, and manage computerized raw material data and can print sales reports and the entry and exit of raw materials easily.